In vitro comparison of renal handling and uptake of two somatostatin receptor-specific peptides labeled with indium-111 - Trejtnar, Frantisek; Novy, Zbynek; Petrik, Milos; Laznickova, Alice; Melicharova, Ludmila; Vankova, Marie; Laznicek, Milan (Annals of nuclear medicine, 2008)
OBJECTIVE: Radiolabeled receptor-specific somatostatin analogs labeled with gamma- or beta-emitting radionuclides are useful for scintigraphic imaging and/or therapy of selected neuroendocrine tumors. However, significant renal uptake may result in radiotoxicological injury of the kidney and can limit clinical application of the agents. The aim of the study was to analyze renal handling, rate, and mechanism of renal accumulation of two somatostatin receptor-targeted peptides, [DOTA(0), Tyr(3), Thr(8)]-octreotide (DOTA-TATE) and [DOTA(0), 1-Nal(3)]-octreotide (DOTA-NOC), labeled with indium-111 using in vitro methods. METHODS: The perfused rat kidney and freshly isolated rat renal cells were used as experimental models. The perfusion was performed in a recirculation regimen at constant pressure with solution containing bovine albumin, erythrocytes, and a mixture of essential substrates. The renal cells were isolated from rat kidneys using two-phase collagenase perfusion. Accumulation studies were used to evaluate the renal uptake of the peptides and to compare their accumulation with that of passively or actively transported model drugs. The influence of selected inhibitors of receptor-mediated endocytosis and the inhibition of energy-dependent transport processes on the uptake were also investigated using isolated renal cells. RESULTS: The renal clearance of (111)In-DOTA-NOC in the perfused rat kidney was significantly lower than that of (111)In-DOTA-TATE. Reverse situation was found in the case of renal retention. Pretreatment of the perfused kidney with maleate markedly decreased the renal retention. (111)In-DOTA-NOC was accumulated in the isolated renal cells at a higher rate than (111)In-DOTA-TATE (ratio 3: 1). The uptake of the radiopeptides in renal cells was higher than the uptake of not only the passively transported sucrose but also actively transported and accumulated methylglucose. The rank order of potency to inhibit the uptake by active endocytosis was approximately aprotinin > maleate > lysine. The uptake of the radiopeptides in the renal cells was temperature dependent. CONCLUSIONS: Both in vitro methods showed a higher renal accumulation of (111)In-DOTA-NOC in comparison with (111)In-DOTA-TATE. The renal uptake was partly decreased by inhibitors of receptor-mediated endocytosis and by a block of energy-dependent processes. A significant participation of active transport processes in renal accumulation of the studied peptides was confirmed.
Keywords: Metabolic Clearance Rate; Sensitivity and Specificity; senzitivita a specificita; ledviny; tkáňová distribuce; receptory somatostatinu; metabolická clearance; Kidney; krysa rodu Rattus; oktreotid; Organometallic Compounds; zvířata; Cells, Cultured; potkani Wistar; reprodukovatelnost výsledků; Octreotide; organokovové sloučeniny; Rats, Wistar; Male; Reproducibility of Results; kultivované buňky; Receptors, Somatostatin; Radionuclide Imaging; Rats; Animals; mužské pohlaví; radiofarmaka; radioisotopová scintigrafie; Tissue Distribution; Radiopharmaceuticals